The role of zinc in the premature brain: functions, outcomes and future research perspectives - Chamakioti, Myrsini; Brion, Luc P.; Viswanathan, Pranav; Lair, Cheryl S.; Angelis, Dimitrios (Frontiers in Pediatrics, 2024)
Zinc (Zn) is one of the most prevalent and essential micronutrients, found in 10% of all human proteins and involved in numerous cellular enzymatic pathways. Zn is important in the neonatal brain, due to its involvement in neurotransmission, synaptic plasticity, and neural signaling. It acts as a neuronal modulator and is highly concentrated in certain brain regions, such as the hippocampus, and the retina. Low Zn intake is frequent in several countries and in populations with high poverty index. Preterm infants are at risk for Zn deficiency for prenatal (missing fetal Zn) and postnatal reasons (less intestinal absorption and insufficient intake in maternal milk to match fetal accretion). The amount of Zn needed for preterm infants is not known and remains the subject of controversy. Recent nutritional recommendations favored an increase in daily Zn supplementation. Systematic reviews of randomized trials have shown that Zn supplementation in preterm infants increases weight gain and may decrease mortality. In this review we will summarize the role of Zn in brain functions and outcomes in preterm newborns, gaps in knowledge and areas of future research.